Performance Evaluation of Al-Rustamiya Wastewater Treatment Plant - AbdulKarim Muneer AbdulRazzak (Journal of Engineering, 2023)
Al-Rustamiya sewage treatment plant (WWTP) serves the east side of Baghdad city (Rusafa) and is considered one of the largest projects.It consists of three parts (old project F0, first extension F1, and second extension F2) that treat wastewater and the effluent is discharged into Diyala river and thus into the Tigris River. These plants are designed and constructed with an aim to manage wastewater to reachIraqi effluent standard for BOD5, COD, TSS and chloride concentrations of 40, 100, 60 and 600 mg/L respectively. The data recordedfrom March till December 2011 provided from Al-RustamiyaWWTP, were considered in this study to evaluate the performance of the plant. The results indicated that the strength of the wastewater entering the plant varied from medium to high. The average concentrations of the effluent of BOD5, COD, TSS and chloride were within Iraqi effluent standards. The overall efficiency removalswere: For BOD5: 92.1, 90.31, and 92.96% for F0, F1, and F2 respectively COD: 88.23, 87.9, and 87.95% for F0, F1, and F2 respectively TSS: 86.98, 80.72, and 89% for F0, F1, and F2 respectively Chloride: 14.79, 15.37, and 15.31% for F0, F1, and F2 The mean value of BOD5/COD ratio of the raw wastewater was 0.67 as for typical untreated domestic wastes. The mean BOD/COD ratios of the treated sewage from F0 was 0.48, from F1 0.50 and from F2 0.38. These ratios did not confirm with the typical ratios indicating that the wastewaterneeds more treatment